Inclusive Management in Public Administration: The Development of a Work-Centred Training Program - Almeida, Beatriz; Cadilhe, Maria; Pereira, Cláudia; Santos, Marta (Relations industrielles / Industrial Relations, 2025)
In this article, we aim to understand how a training program can help managers promote inclusive management. We present the development and implementation of a work activity-centred training program for inclusive management in an institution of the Portuguese Public Administration. Using a mixed design-based research methodology, we brought 24 municipal managers into the development and implementation phases of the training program. We organized a focus group of managers to understand their experiences, constraints and training needs for the promotion of inclusive management in their work activity. Questions were put to them before, during and after program implementation. To promote inclusion actions in their work activity, we developed a 60-hour b-learning program. Our findings show the effectiveness of integrating work activity analysis and group reflection when co-creating the training program with participating managers to help them act in their work activity and meet the challenges of inclusive management. The managers reported they had improved their knowledge and resources for inclusive management in their work activity, particularly by thinking and creating together as a group. They valued the participatory and context-specific approach. We conclude that work activity-centred training programs can be key to enhancing the ability of managers to promote inclusive management. The participatory design fostered group learning, grounded in real work contexts, and helped the managers develop inclusion strategies. We provide insights into how inclusive management can be developed collectively, thereby showing the importance of collaboration between Academia and Public Institutions in the development of training programs.